Preconditioning methods for high‐order strongly stable time integration methods with an application for a DAE problem. Issue 6 (16th September 2015) - Axelsson, Owe; Blaheta, Radim; Kohut, Roman
Summary: High‐order strongly stable time integration method enables use of large time steps and is applicable also for differential–algebraic problems, without any order reduction. At each time step, frequently a large‐scale linear algebraic system must be solved. To solve the arising block matrix systems, an efficient preconditioning method is presented and analysed. The method is applied for the solution of a consolidation problem arising in poroelasticity. Copyright © 2015 John Wiley & Sons, Ltd.